TRANSFORMATION THE INVESTMENT POLICY OF UKRAINE IN THE CONTEXT OF NON-STATIONARY ECONOMY: MONITORING OF MACROECONOMIC INDICATORS - KARPENKO, Lidiia; IZHA, Mykola (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The paper proposes the use of modern tools for monitoring macroeconomic indicators and the study of their non-stationary dynamics in the context of the implementation of investment policy based on the tools of phase and cointegration analysis, which makes it possible to obtain a comprehensive assessment and analyze the stability of the macroeconomic dynamics of Ukraine in the context of increasing globalization transformations in the dynamics of territorial development, ongoing in the conditions of global crisis processes. This study is aimed at identifying and assessing the factors (determinants) that affect the inflow of foreign direct investment into the regions of Ukraine. The paper examined the factors that have a significant impact on the volume of foreign direct investment. To verify the hypotheses, an economic-mathematical model with fixed effects is proposed.